Sex-Specific Clinical Characteristics and Long-Term Outcomes in Patients With Myocardial Infarction With Non-obstructive Coronary Arteries - Gao, Side; Ma, Wenjian; Huang, Sizhuang; Lin, Xuze; Yu, Mengyue (Frontiers in Cardiovascular Medicine, 2021)
Background: Sex differences in clinical profiles and prognosis after acute myocardial infarction have been addressed for decades. However, the sex-based disparities among patients with myocardial infarction with non-obstructive coronary arteries (MINOCA) remain largely unreported. Here, we investigated sex-specific characteristics and long-term outcomes in MINOCA population. Methods: A total of 1,179 MINOCA patients were enrolled, including 867 men and 312 women. The mean follow-up was 41.7 months. The primary endpoint was a composite of major adverse cardiovascular events (MACE), including all-cause death, non-fatal reinfarction, revascularization, non-fatal stroke, and hospitalization for unstable angina or heart failure. Baseline data and outcomes were compared. Kaplan-Meier curves and Cox regression analyses were used to identify association between sex and prognosis. Results: Female patients with MINOCA had more risk profiles with regard to older age and higher prevalence of hypertension and diabetes compared with men. The evidence-based medical treatment was similar in men and women. The incidence of MACE (men vs. women: 13.8 vs. 15.3%, p = 0.504) did not differ significantly between the sexes. The Kaplan-Meier analysis also indicated that women had a similar incidence of MACE compared to men (log rank p = 0.385). After multivariate adjustment, female sex was not associated with the risk of MACE in overall (adjusted hazard ratio 1.02, 95% confidence interval: 0.72–1.44, p = 0.916) and in subgroups of MINOCA patients. Conclusion: The long-term outcomes were similar for men and women presenting with MINOCA despite older age and more comorbidities in women. Future research should aim to improve in-hospital and post-discharge care for both sexes with MINOCA.